Podcasts for Nonformal Learning: Using Social Media for Creating Personal Learning Environments, Personal Learning Networks - Stonkienė, Marija; Janiūnienė, Erika (Information & Media, 2020)
The use of second-generation web technology (WEB2) in education is emphasising the role of social media as educational sources.Researchers that are analysing personal learning environments (Schaffert, Kalz, 2009; Dabbagh, Kitsantas, 2012), personal learning networks (Couros, 2010) suggest the importance of social media, although this emphasis is attributed to the collaborative interaction of learners. To comprehensively assess the potential of podcasts as social media in the creation of personal learning environments, personal learning networks, the research described in this article does not restrict the definition of podcasts as the potential of collaboration provided by social media. In this article, attention is directed towards the potential of podcasts in the creation of personal learning environment and personal learning networks.By using integrated information behaviour module analysis to determine if the students of Lithuanian higher education institutions value the potential of informal learning provided by podcasts. To determine if these technologies are used for the formation of personal learning environments, personal learning networks, a discussion group research was conducted. During the research the analysis of participant podcast usage showed there is interaction between media content used for recreation and media content used for formal and informal learning. This means that the participants of the research use podcasts to create personal learning environments.On the other hand, this interaction is minimal, created only by the learners and reasoned by the search of educational podcasts. The analysis of the experiences of the discussion participants revealed that the collaborative interaction between learners involved in the research in searching, sharing and using podcasts in the process of learning is not intensive, it is typically fragmented. This allows to point out that the communities that use podcasts for informal learning are not forming. This shows that the potential of podcasts in creating a learning network is not fulfilled, and that podcasts don’t inspire participatory learning.
Keywords: social media; podcasts; technology-based learning; informational behavior; personal learning environment; personal learning network